Halophyte Artemisia caerulescens L.: Metabolites from In Vitro Shoots and Wild Plants - Ylenia Pieracci; Martina Vento; Luisa Pistelli; Tiziana Lombardi; Laura Pistelli (Plants, 2022)
Halophyte plants are potential resources to deal with the increasing soil salinity determined by climatic change. In this context, the present study aimed to investigate the germplasm conservation of Artemisia caerulescens collected in the San Rossore Estate (Pisa, Italy) through in vitro culture, biochemical properties, and the phytochemical composition of the volatile fraction of both in vitro shoots and different organs of wild plants (leaves, young and ripe inflorescences). The best medium tested for the shoot proliferation was MS, with the addition of 1 μM BA. Total polyphenol content and antioxidant activity were noticeable in both the inflorescences, while leaves and in vitro shoots showed lower amounts. Concerning the phytochemical investigation, the headspaces (HSs) and the essential oils (EOs) were characterized by oxygenated monoterpenes as the main chemical class of compounds in all samples, and with α- and β-thujone as the major constituents. However, the EOs were characterized by noticeable percentages of phenylpropanoids (23.6–28.8%), with brevifolin as the unique compound, which was not detected in the spontaneous volatile emissions of the same parts of the wild plant. Good amounts of EOs were obtained from different organs of the wild plant, comprising between 0.17% and 0.41% of the young and ripe inflorescences, respectively.